Analysis of the Impact of Rising Fuel Prices and the Depreciation of the Rupiah on the Profitability and Sustainability of MSMEs - Dony Hidayat; Sri Sahbany; Lalu Adiyatma Taopikul Hadi; Nur Fitrianingsi (Journal of Trends Economics and Accounting Research, 2026)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are vital for economic growth but are inherently vulnerable to macroeconomic shocks. Specifically, volatility in fuel prices and national currency depreciation threaten their operational profitability and long-term sustainability, particularly in rural contexts with limited financial buffers. This study aims to analyze the impact of rising fuel prices and the depreciation of the Rupiah on the profitability and sustainability of MSMEs in Ungga Village, Praya Barat Daya Subdistrict, Central Lombok Regency, Indonesia. A quantitative, cross-sectional design was employed, surveying 216 MSME owners using structured questionnaires. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the causal relationships between the variables. The findings reveal that rising fuel prices have a significant negative impact on both profitability (β=−0.48, p<0.001) and sustainability (β=−0.35, p<0.001). Similarly, the depreciation of the Rupiah significantly negatively affects profitability (β=−0.25, p=0.002) and sustainability (β=−0.18, p=0.041). Macroeconomic shocks directly undermine the financial performance and long-term viability of MSMEs in Ungga Village. The study highlights an urgent need for targeted policy interventions, such as financial management support and cost-mitigation strategies, to enhance the resilience of rural MSMEs against external economic volatility.